23 Uncovering the Molecular Mechanisms of Patent Foramen Ovale. (20th November 2012) - Elliott, GC; Gurtu, R; Newman, W; McCollum, C; Wang, T
Abstract : Patent Foramen Ovale (PFO) is a cardiac developmental defect present in 25% of the general population. It is a major risk factor in cryptogenic stroke and migraine. PFO occurs when the Foramen Ovale (FO), a valve-like passageway in the foetal heart allowing blood to bypass the lungs, fails to fuse shut remaining open into adulthood. Evidence suggests PFO has a genetic predisposition. Genetic variants associated with PFO would serve as biomarkers used for screening high risk individuals. Specific genes that contribute to FO closure are largely unknown. This is attributed to our incomplete understanding of the physiological process of FO closure. To investigate the molecular mechanisms underlying FO closure, gene expression and histological analysis is being performed using rats as a model. For the first time histological analysis of heart tissue sections from rats aged E20 to P7 have uncovered specific contributions of septum primum and se cundum to FO closure. Results from immunostaining of marker genes including vimentin, SM alpha-actin and CD-31 have suggested endothelial-to-mesenchymal transition (EndMT) occurs in this process. Based on the fact that patients who have CADASIL, a genetic stroke syndrome caused by NOTCH3 gene mutations, have a high prevalence (80%) of PFO; and that Notch signalling is a critical player in EndMT, immunohistochemical staining of FO regions for genes of the Notch signalling pathway have been carried out. Preliminary results showed specific expression patterns of these genes in FO region. We conclude that FO closure is a process of EndMT with the involvement of Notch signalling.